Competition and inclusive regional economic growth in food production: Barriers to entry and the role of African multinational corporations - Teboho Bosiu; Thando Vilakazi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The growth of African multinational companies in Southern and East Africa in recent decades brings with it a great opportunity for development of productive capacity in the region and greater regional integration. This study identifies three emerging multinationals in the region- Trade Kings (from Zambia), Export Trading Group (Kenya), and Mount Meru (Tanzania)-that have developed capabilities over time to become effective competitors of incumbent food production companies in other country markets. By analysing the history, growth, competitive strategies, and capabilities of the firms, the study identifies factors that appear to have shaped their expansion in the region and the key lessons from their experiences. Drawing from interviews and publicly available information, the paper also analyses the various constraints the companies have faced in growing their businesses, particularly across borders in the region, with a view to identifying opportunities for policy that might help such companies to grow production capacity in local economies.
Keywords: L11; L14; L41; L52; 330; African multinational corporations; barriers to entry; food production; regional integration